Päiväkirurgisten sairaanhoitajien kokema työn sisäinen hallinta - Mäkelä, Anna-Maria (Turun yliopisto, 2002)
[Abstract]: The experiences of staff empowerment by day surgery nurses.
Keywords: Ambulatory Surgical Procedures : nursing; Attitude; Nursing Staff, Hospital; Power, Psychological